(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
There are some types of small businesses that are found almost everywhere. One of these businesses is a street food business, ready-to-eat food, or drinks sold on sidewalks and other public places such as markets or in a fair. These kinds of businesses are often in food booths or carts that are commonly prepared on hand for immediate consumption. Due to its diversity, many find these businesses ceaseless to subdue. In urban areas, these businesses include small-scale businesses from which vendors get benefits perceived to be usual. Thus, street food has been widely tolerated among the community. For many years, no particular laws are mandated vendors in terms of their responsibilities to ensure that the food they offer is free from any contamination. This study used a descriptive research design and survey to easily gather the data needed in the pre-test and post-test. The respondents of the study were 50 grade 12 Accountancy, Business, and Management students that were selected through the convenience sampling technique. The results of the study revealed that improving the hygiene and sanitation of sidewalk vendors positively affected the customers’ satisfaction of grade 12 students in terms of (1) cleanliness of food (freshness and proper sanitation of food can avoid the contamination of the product in bacteria), (2) cleanliness of the vendor (having personal cleanliness of vendor and wearing proper attire when cooking can make sure that the food is clean and safe to eat), and (3) cleanliness of area/stall (cleaning the area regularly can reduce food contamination. The results demonstrated the need for the teachers and school administrators to guide the Bestlink students on the street foods they consume outside the school. The results of the study showed that the cleanliness of the food depends on how the vendors prepare the food. Having personal hygiene and wearing proper attire when cooking can avoid food contamination.